2013
DOI: 10.3136/fstr.19.691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying on Creatine/Creatinine Ratios and Subsequent Taste of Herring (Clupea pallasii) Fillet

Abstract: This study was conducted to investigate the effect of drying time on creatine/creatinine ratios, and subsequently taste of herring fillet. Creatine and creatinine contents were quantified during drying of herring fillet by hydrophilic interaction liquid chromatography (HILIC) and their effect on sensory perception was determined. Results showed that creatine content decreased significantly (p < 0.05), while creatinine content increased during the drying period. Creatinine/creatine ratio of herring fillet incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The fact that creatine and creatinine concentrations were not different before and after freeze‐drying is in correspondence with literature data (Harris et al., ; Shah et al., ), where it was demonstrated that neither freeze‐drying nor air‐drying influences the concentrations of both molecules in a sample. This result also indicates that this gentle drying method is suitable to preserve and store samples for later creatine analysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The fact that creatine and creatinine concentrations were not different before and after freeze‐drying is in correspondence with literature data (Harris et al., ; Shah et al., ), where it was demonstrated that neither freeze‐drying nor air‐drying influences the concentrations of both molecules in a sample. This result also indicates that this gentle drying method is suitable to preserve and store samples for later creatine analysis.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the rather high number of samples together with the broad spectrum of chosen diets and components supplies a reliable picture, especially when raw and processed feedstuffs are compared. The fact that creatine and creatinine concentrations were not different before and after freeze-drying is in correspondence with literature data (Harris et al, 1997;Shah et al, 2013), where it was demonstrated that neither freeze-drying nor air-drying influences the concentrations of both molecules in a sample. This result also indicates that this gentle drying method is suitable to preserve and store samples for later creatine analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…myoglobin hemoglobin heme , , A, B, C, , (Park et al, 1985 (Mok et al, 2008;Gao et al, 2014;Agustinelli and Yeannes, 2015a), (Zhang et al, 2012;Hu et al, 2015;Kim et al, 2016) (Inoue et al, 1971;Luo et al, 2010;Azad Shah et al, 2013;Agustinelli and Yeannes, 2015b) , (MFDS, 2016) . , 2016 7-10 .…”
mentioning
confidence: 99%